The Oxford Handbook of Prehistoric Figurines - Timothy Insoll (Les Carnets de l’ACoSt)
Figurines dating from prehistory have been found across the world but have never before been considered globally. The Oxford Handbook of Prehistoric Figurines is the first book to offer a comparative survey of this kind, bringing together approaches from across the landscape of contemporary research into a definitive resource in the field